The Geoscience of Climate and Energy 1. Understanding the Climate System, and the Consequences of Climate Change for the Exploitation and Management of Natural Resources: The View from Banff - Miall, Andrew; Miall, Charlene (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2009)
SUMMARY A commonly expressed opinion within the earth-science community is that the work of the Intergovernmental Panel on Climate Change (IPCC) has largely ignored paleoclimate data and the methods of research utilized by earth scientists. It can be demonstrated that this is not the case, and one of the objectives of the Gussow–Nuna conference was to present current research in this area. Whereas earth scientists might seem ideally placed to address issues of climate change and energy, many of the beliefs that inform public opinion about global warming and climate change are based on misrepresentations or over-simplifications. Six examples are discussed here, including mis-perceptions about the melting and retreat of glaciers, the true causes of concern about the future fate of polar bears, and myths about petroleum pricing and availability. There is ample space for the earth-science community to add its informed voice to debates about energy and climate change, but, to date, this voice appears to be have been largely ineffective.